An effective iris location method with high robustness - Tang, Rongnian; Han, Jiuqiang; Zhang, Xinman (Oficyna Wydawnicza Politechniki Wrocławskiej, 2007)
Now, iris recognition is a topical issue. This paper focuses on iris location, which is an important stage in iris recognition, and develops a new method for that purpose. Use has been made of dilation operator in order to suppress the interference of eyelash, and support vector machines (SVM) classifier has been employed to identify the iris boundary. The results of experiment carried out on iris image database showed the method proposed to have an encouraging performance. Compared with the traditional methods, those of Daugman and Wildes, this method offers a higher correct location ratio and is more computationally efficient.
Optica Applicata, Vol. 37, 2007, nr 3, s. 295-303
Keywords: optyka; iris location; boundary recognition; support vector machines (SVM)